1999
DOI: 10.1523/jneurosci.19-10-04065.1999
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Brain Gray and White Matter in Healthy Young Adults: Correlations with Cognitive Performance

Abstract: Sex-related differences in behavior are extensive, but their neuroanatomic substrate is unclear. Indirect perfusion data have suggested a higher percentage of gray matter (GM) in left hemisphere cortex and in women, but differences in volumes of the major cranial compartments have not been examined for the entire brain in association with cognitive performance. We used volumetric segmentation of dual echo (proton density and T2-weighted) magnetic resonance imaging (MRI) scans in healthy volunteers (40 men, 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

69
541
11
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 812 publications
(632 citation statements)
references
References 62 publications
69
541
11
11
Order By: Relevance
“…Recently, we have reported double dissociations between facial morphology and neuropsychological test performance in normal subjects: the shape of the anterior face covaried with spatial attention/visuomotor tracking in men but not women, and with verbal fluency in women but not men (Hennessy et al 2005(Hennessy et al , 2006; these findings complement evidence that men perform better than women on visuospatial tasks, while women perform better than men on verbal tasks (Caplan et al 1997;Gur et al 1999). Such relationships constitute strong evidence that the well established, intimate embryological relationship between facial and anterior brain morphogenesis extends to anterior brain function in adults, in a sex-specific manner.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, we have reported double dissociations between facial morphology and neuropsychological test performance in normal subjects: the shape of the anterior face covaried with spatial attention/visuomotor tracking in men but not women, and with verbal fluency in women but not men (Hennessy et al 2005(Hennessy et al , 2006; these findings complement evidence that men perform better than women on visuospatial tasks, while women perform better than men on verbal tasks (Caplan et al 1997;Gur et al 1999). Such relationships constitute strong evidence that the well established, intimate embryological relationship between facial and anterior brain morphogenesis extends to anterior brain function in adults, in a sex-specific manner.…”
Section: Discussionsupporting
confidence: 62%
“…diastolic MCA velocity) compared with men, which has been well documented (9,43,64,67). It has also previously been shown that premenopausal women have greater resting brain blood flow compared with age-matched men (despite a smaller brain mass) (19,20). This could be a result of the vasodilatory effects of estrogen on the cerebrovascular endothelium (47).…”
Section: Discussionmentioning
confidence: 82%
“…This differs from some reports of less neurocognitive impairment in women than men with schizophrenia (Goldstein et al 1998;Hoff et al 1996), or more impairment in women than men (Lewine et al 1996), but is consistent with earlier reports from our center reporting similar impairment in male and female patients. The difference favoring women with schizophrenia for verbal memory and men for spatial processing may reflect normal sex differences in these domains (Bleecker et al 1988;Gur et al 1999aGur et al ,2001Kimura and Harshman 1984;Kramer et al 1988). Thus, it seems that although clinical measures favoring women do correlate with neurocognitive functioning, the effect is not sufficient to produce a group difference in neuropsychological performance.…”
Section: Study 2: Discussionmentioning
confidence: 99%